The European Insomnia Guideline: An update on the diagnosis and treatment of insomnia 2023 - Riemann, Dieter; Espie, Colin A.; Altena, Ellemarije; Arnardottir, Erna Sif; Baglioni, Chiara; Bassetti, Claudio L. A.; Bastien, Celyne; Berzina, Natalija; Bjorvatn, Bjørn; Dikeos, Dimitris; Dolenc Groselj, Leja; Ellis, Jason G.; et al. (Journal of sleep research, 2023)
Summary Progress in the field of insomnia since 2017 necessitated this update of the European Insomnia Guideline. Recommendations for the diagnostic procedure for insomnia and its comorbidities are: clinical interview (encompassing sleep and medical history); the use of sleep questionnaires and diaries (and physical examination and additional measures where indicated) (A). Actigraphy is not recommended for the routine evaluation of insomnia (C), but may be useful for differential‐diagnostic purposes (A). Polysomnography should be used to evaluate other sleep disorders if suspected (i.e. periodic limb movement disorder, sleep‐related breathing disorders, etc.), treatment‐resistant insomnia (A) and for other indications (B). Cognitive‐behavioural therapy for insomnia is recommended as the first‐line treatment for chronic insomnia in adults of any age (including patients with comorbidities), either applied in‐person or digitally (A). When cognitive‐behavioural therapy for insomnia is not sufficiently effective, a pharmacological intervention can be offered (A). Benzodiazepines (A), benzodiazepine receptor agonists (A), daridorexant (A) and low‐dose sedating antidepressants (B) can be used for the short‐term treatment of insomnia (≤ 4 weeks). Longer‐term treatment with these substances may be initiated in some cases, considering advantages and disadvantages (B). Orexin receptor antagonists can be used for periods of up to 3 months or longer in some cases (A). Prolonged‐release melatonin can be used for up to 3 months in patients ≥ 55 years (B). Antihistaminergic drugs, antipsychotics, fast‐release melatonin, ramelteon and phytotherapeutics are not recommended for insomnia treatment (A). Light therapy and exercise interventions may be useful as adjunct therapies to cognitive‐behavioural therapy for insomnia (B).